Analisa Sistem e-Commerce Pada Perusahaan JNE - Indonesia - Darojat, Tubagus Ahmad (Forum Kerjasama Pendidikan Tinggi, 2019)
Technology at this time is very influential in helping humans in their daily lives both in the household, industrial and personal activities. E-Commerce is an online buying and selling activity that is marketed through online sites, social media or web sites. JNE is the largest company in Indonesia in freight forwarding services that gets a big profit because of E-Commerce, because the more people who use the internet the greater the chance for companies to make E-Commerce and one of them JNE makes E-Commerce within the scope of buying and selling food in Website form with the title PESONA (Souvenir Order) which aims to facilitate the public in buying souvenirs or snacks typical food from every corner of the archipelago in Indonesia.